Rôle de l’action collective et du capital social dans les processus d’adaptation au changement climatique en zone côtière - Comparaison de deux études de cas au Nouveau-Brunswick (Canada) - Mélinda Noblet; Julie Guillemot; Omer Chouinard (Développement Durable et Territoires)
This article focuses on the role of social capital in the context of the implementation of adaptation strategies to climate change in the building sector in coastal areas. Our work focuses on two case studies located in the North (Pigeon Hill and Cap Bateau) and South (Cocagne and Grande Digue) New Brunswick (Canada). We observe that mobilizations are based on social capital such as family ties or associative links. However, the scope of these mobilizations remains relatively limited because of the weakness of the local governance process in New Brunswick. In order to develop a real capacity for local action, it would be necessary to rethink the synergy between the scales and modes of action. This would allow the social capital -necessary to the local adaptation process- to rely on supra-local resources and structures.